양상전근 마비의 임상 양상 및 수술 결과 - 박현주; Hyun Ju Park; 이종복; Jong Bok Lee; 유수리나; Soolienah Rhiu (Daihan angwa haghoi jabji, 2014)
목적: 양상전근 마비의 임상 양상 및 수술적 치료의 결과에 대해 알아보고자 하였다. 대상과 방법: 1999년부터 2012년까지 연세대학교 세브란스 의료원 안과에 내원하여 양상전근 마비로 진단받고 수술적 치료를 시행한 모든 환자들을 대상으로 후향적인 조사를 진행하였다. 결과: 총 15명의 환자 중 7명은 남성, 8명은 여성이었으며 첫 사시 교정 수술을 시행한 평균 연령은 14.6세였다. 모든 환자들은 1차 사시 교정 수술로서 하직근 후전술을 시행 받았다. 9명(60.0%)의 환자에서 2차 교정수술이 필요했으며, 이 중 4명은 수평근 전위술, 2명은 외사시 교정술, 그리고 3명에서는 하사시와 외사시 교정술을 동시에 시행하였다. 수술 전 평균 하사시는 29.9 ± 8.4 PD였으며 수술 후 평균 4.7 ± 5.3 PD로 감소하였다. 평균 경과 관찰 기간은 40.9개월이었다. 7명(46.7%)의 진성 안검하수 환자에서 안검하수교정술을 시행하였다. 최종 경과 관찰 시 11명 중 8명의 환자에서 약시가 없거나 경도의 약시만 남았다. 결론: 일차적으로 하직근 후전술을 단독으로 시행하거나 추가적으로 이차적인 근전위술을 시행하여 양상전근 마비의 치료에서 효과적인 결과를 얻었다. 이번 연구를 통해 분석한 양상전근 마비의 임상 양상 및 수술 결과는 환자의 적절한 치료 방법 설정 및 예후 예측에 도움이 될 것으로 생각한다. Purpose: To evaluate the clinical manifestations of double elevator palsy and describe the surgery outcomes in patients. Methods: We performed a retrospective chart review of all patients who were treated surgically for double elevator palsy between 1999 and 2012 at Yonsei University, Severance Hospital in Seoul, Korea. Results: Overall, 15 subjects (7 males and 8 females) with a mean age of 14.6 years (range, 3-40 years) underwent their first surgery during the study period. All patients received inferior rectus recession as a primary procedure. Nine patients (60.0%) underwent a secondary procedure which included 4 cases of horizontal muscle transposition, 2 cases of correction of exotropia, and 3 cases of correction of hypotropia and exotropia simultaneously. The mean preoperative hypotropia was decreased from 29.9 ± 8.4 prism diopter (PD) to 4.7 ± 5.3 PD postoperatively. Mean follow-up period was 40.9 ± 48.2 months. Seven patients (46.7%) underwent eyelid surgery for true ptosis. At last follow-up, a majority of patients showed mild or no amblyopia. Conclusions: Primary inferior rectus recession and additive secondary horizontal muscle transposition surgery was effective in treatment of double elevator palsy. The clinical manifestations and surgical outcomes of monocular elevation deficiency in the present study can help in the treatment of Korean patients. J Korean Ophthalmol Soc 2014;55(11):1674-1680